Analysis of Partially Shaded PSPICE - PV Modules for Series- Parallel and TCT Configuration - Kubba, Zainab M (Al-Nahrain Journal of Science, 2018)
The present work is a study of effects of partial shading on the performance of a PV module spatially on the maximum power point position. This paper clarifies the mechanism of partial PV shading on a number of PV module connected in series parallel and total cross tide. In series parallel connection the shading effects will be studied for deferent number of module. Also this search was mainly devoted to investigate the performance comparison between series parallel and total cross tide with bypass diode and without. A PSPICE simulation model that represents 36 cells PV module has been used to test this study and results are presented.